Ribbon of Peace Banners in Front of Sisk Federal Courthouse - Watkins, Howard::::::::: (1985)
Albert Watkins, Christine Watkins, Adam Watkins and Howard Watkins holding Robin Watkins in front of Sisk Federal Courthouse